The loneliest number: small sample sizes result in taxonomic changes in Okanagana (Hemiptera: Auchenorrhyncha: Cicadidae: Tibicininae) - Chatfield-Taylor, Will; Montelongo, Denise (Zootaxa, 2026)
The genus Okanagana has several outstanding taxonomic issues which stem largely from the poor descriptions and small type series commonly used in the early 20th century. Here we address two known issues; relegating a former species to a junior subjective synonym and resurrecting a previously synonymized species. Okanagana napa Davis, 1919 was described from a single specimen but using morphology and other lines of evidence we identify it as conspecific with O. arboraria Wymore, 1934 n. syn. making the latter a junior subjective synonym. Okanagana albibasalis stat. rev. was improperly synonymized with O. canescens Van Duzee, 1915 and is revised to full species status based on their differing morphologies. We also provide corrections to the phylogenetic hypothesis in Cole et al. (2023) that result from these taxonomic acts.